Enhanced Electrochemical Performance of Mesocarbon‐Microbeads‐Based Anodes through Air Oxidation for Sodium‐Ion Batteries. Issue 10 (14th July 2017) - Yuan, Chao; Zhu, Youyu; Zhao, Pinyi; Yu, Baojun; Li, Qi; Wang, Chengyang
Abstract: Air oxidation is introduced as a simple and feasible method of modification for mesocarbon microbeads (MCMBs), which improves the electrochemical performance of MCMBs as anodes for sodium‐ion batteries (SIBs). Optimal oxidation conditions are explored. Green MCMBs, initially oxidized at 360 °C then carbonized (OC‐MCMB360), exhibit a high reversible capacity up to 286 mAh g −1 at a current density of 25 mA g −1 . In addition, the OC‐MCMB360 sample also presents an excellent rate performance with 79 mAh g −1 at a current density of 3.2 A g −1 and a considerable reversible capacity of 166 mAh g −1 after 100 cycles at 100 mA g −1 . The larger interlayer spacing and increased defect sites caused by oxidation contribute to the enhanced electrochemical performance of oxidized MCMBs in SIBs. Abstract : What's in store : Inspired by the stabilization process for carbon fibers, air oxidation is introduced as a modification for mesocarbon microbeads (MCMBs). The introduction of oxygen atoms contribute to the crosslinking between carbon layers and adjust the disorder degree of MCMBs by increasing defect sites. The larger interlayer spacing and increased defect sites caused by oxidation are beneficial for MCMBs to store and transfer sodium ions.